Validação tecnológica do caroço do fruto do açaí como material alternativo na pavimentação de baixo volume de tráfego - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
Manaus is located on the Alter do Chão formation consists primarily of sandstone, sandstone here called Manaus. This sedimentary formation has enormous difficulties obtaining stone material in that region, and does not respond positively to the mechanical tests is approximately 10 feet below ground, making it difficult to extract. As a solution has been the use of natural resources usually employed in running jackets knitwear regional road, the boulder river, which in addition to negatively impact the environment at the time of extraction, is not the best material to be used in mixtures asphalt. All this problematic for obtaining the coarse aggregate directly impacts the quality of the pavement, his absence causes the excessive presence of permanent deformation and fatigue cracking in the surface layer of pavement locations. How can environmentally and economically correct solution for this case is analyzed here using the core of the fruit of the Acai (Euterpe of request) as aggregate in asphalt mixtures participant Amazonian capital. The acai berry is a fruit widely consumed by the population, part of the local tradition, has a spherical shape, 10 % of its constitution is pulp, leaving 90 % for the core, after extraction of the pulp it constitutes environmental liability. Your participation in the asphalt mixture was partially, not totally replaced the coarse aggregate in it. As aggregate secondary used to the construction and demolition waste (CDW ) as aggregate opted to use a residual sand sold in Manaus, portland cement CP II - Z - 32 as filler cap and 50/70 provided by Manaus Refinery. The composites were characterized mixing and mechanical analysis was performed by means of Tensile Strength by Diametral Compression Module and Resilience. The experiments were marked by the standards of the National Department of Transport Infrastructure ( DNIT ), American Society For Testing and Materials (ASTM ) and American Association of States Highway Officials ( AASHTO ). The results of inserting the core of acai as aggregate in asphalt mixture proved satisfactory when compared to other types of mixtures used , applying the process of low traffic volume .
Keywords: Pavimentos de asfalto; Açai – Semente; Agregados (Materiais de construção); Mistura asfáltica; Baixo volume de tráfego; ENGENHARIAS